PENGARUH PEKERJA MIGRAN INDONESIA TERHADAP PEMBANGUNAN DESA DI PROVINSI BALI - admin, jekt; Antara, I Nyoman Candra; Sukadana, I Wayan (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 13 No 5 (2024): Vol.13.No.5. MEI 2024 [307-392], 2024)
This study aims to determine the influence of Indonesian Migrant Workers (PMI) on village development in Bali Province. In analyzing village development, the Independent Village Index (IDM) is used with the main variable namely the existence of PMI, supported by control variables in the form of electricity, fuel energy, landfills, latrines, feces final disposal sites, toilets, sources of drinking water, and sources of toilet water. Research data was obtained from PODES 2018, with a total of 777 observations. The data analysis technique used is multiple linear regression analysis with the help of the STATA application. From the results of data analysis, it was concluded that the existence of villagers working as PMI had not been able to have a significant influence on village development in the Province of Bali. This is reflected in the results of data analysis on the developing village index where the research results show that there is still inequality between villages which causes disparities in accessing resources, especially clean water, availability of disposal sites, and from the use of electricity and fuel energy for cooking.   keyword : Household Analysis, Regional Economic Activity, Trade and Labor Market Interactions JEL classification: R2, R11, F16